Impact of New York City's 4-year multi-component natural experiment to improve elementary school physical education on student cardiorespiratory fitness - Hannah R. Thompson; Kristine A. Madsen; Caroline Nguyen; Thomas L. McKenzie; Sally Picciotto (BMC, 2024)
Abstract Background School physical education is an important population-level health intervention for improving youth fitness. This study estimated the impact of New York City's PE Works program - which included providing PE teachers, training for classroom teachers, and administrative/ teacher support for PE - on student cardiorespiratory fitness as measured by the FitnessGram's 15-meter PACER test for aerobic capacity. Methods This longitudinal study (2014/15-2018/19) includes 581 elementary schools (n = 315,999 4th /5th -grade students; 84% non-white; 74% who qualify for free or reduced-price meals, a proxy for socioeconomic status). We apply the parametric g-formula to address schools' time-varying exposure to intervention components and time-varying confounding. Results After four years of staggered PE Works implementation, 49.7% of students/school (95% CI: 42.6%, 54.2%) met age/sex-specific Healthy Fitness Zone (HFZ) aerobic capacity standards set by the FitnessGram. Had PE Works not been implemented, we estimate 45.7% (95% CI: 36.9%, 52.1%) would have met aerobic capacity HFZ standards. Had PE Works been fully implemented in all schools from the program's inception, we estimate 57.4% (95% CI: 49.1%, 63.3%) would have met aerobic capacity HFZ standards. Adding a PE teacher, alone, had the largest impact (6.4% (95% CI: 1.0, 12.0) increase). Conclusion PE Works positively impacted student cardiorespiratory fitness. Mandating and funding multicomponent PE programs is an important public health intervention to increase children's cardiorespiratory fitness.